An advanced LC–MS/MS protocol for simultaneous detection of pharmaceuticals and personal care products in the environment. (14th November 2022) - Yao, Wenrui; Ge, Jinfeng; Hu, Qiaozhuan; Ma, Jingying; Yuan, Daohe; Fu, Xiaoli; Qi, Yulin; Volmer, Dietrich A.
Abstract : Rationale: The development of appropriate analytical screening techniques for pharmaceuticals and personal care products (PPCPs) is the basis for studying the distribution and environmental impact of emerging contaminants (ECs). Mass spectrometry‐based screening methods vary with the complexity of the target compounds. It is challenging to balance both positive and negative ion quantification with a low detection limit. To establish a set of experimental methods including extraction, chromatography‐separation and mass spectrometry screening is one of the most important topics in PPCP research. This paper describes a universal and efficient qualification and quantification protocol for the simultaneous detection of 34 PPCPs in different environmental samples in a single analytical data acquisition run. Methods: Thirty‐four representative PPCPs, which are widely distributed in the environment with high ecological toxicity and complex chemical structures, were selected as representative target ECs. The extraction of the target PPCPs was achieved using only one solid‐phase extraction cartridge without the need to adjust the pH of samples. The enriched samples were detected by LC–MS/MS in both positive and negative ion modes simultaneously. The protocol was evaluated based on the accuracy, precision, detection limits and matrix effects. Results: This method achieved simultaneous detection of PPCPs in both positive and negative ion modes, with a single analytical cycle of 12 min. The observed SPE recoveries were between 40% and 115%. The instrumental detection limits (IDL) varied from 0.01 to 1 pg, and the method detection limits (MDL) were between 0.002 and 3.323 ng/l in different matrices. Most of the PPCPs were subjected to matrix suppression below 30%. The method was successfully applied for quantitative analysis of the PPCPs in different environmental samples, including river samples, wastewater treatment plant (WWTP) samples and soil samples. Conclusions: This protocol developed a rapid and efficient detection method to simultaneous qualitative and quantitative 34 representative PPCPs in the environment. The IDL ranged from 0.01 to 1 pg and the MDL ranged from 0.002 to 3.323 ng/l in different matrices. The detection limit was one order of magnitude lower compared to previous studies. The protocol also provided a wide application range for different environmental matrices, which permitted the migration and transformation of PPCPs to be explored.